Reconfigurable Bioinspired Framework Nucleic Acid Nanoplatform Dynamically Manipulated in Living Cells for Subcellular Imaging - Peng, Pai; Du, Yi; Zheng, Jiao; Wang, Huihui; Li, Tao (Angewandte Chemie International Edition, 2019)
In nature, the formation of spider silk fibers begins with dimerizing the pH‐sensitive N‐terminal domains of silk proteins (spidroins) upon lowering pH, and provides a natural masterpiece for programmable assembly. Inspired by the similarity of pH‐dependent dimerization behaviors, introduced here is an i‐motif‐guided model to mimic the initial step of spidroin assembly at the subcellular level. A framework nucleic acid (FNA) nanoplatform is designed using two tetrahedral DNA nanostructures (TDNs) with different branched vertexes carrying a bimolecular i‐motif and a split ATP aptamer. Once TDNs enter acidic lysosomes within living cells, they assemble into a heterodimeric architecture, thereby enabling the formation of a larger‐size framework and meanwhile subcellular imaging in response to endogenous ATP, which can be dynamically manipulated by adjusting intracellular pH and ATP levels with external drug stimuli. Itsy bitsy spider: To mimic the self‐assembly manner of spider silk proteins, a reconfigurable bioinspired framework nucleic acid nanoplatform has been designed and is dynamically regulated within living cells for lysosome imaging. The dimerization of the DNA structures is pH‐dependent and they enable subcellular imaging in response to endogenous ATP.